The influence of positive and negative electronic word of mouth review on hotel customer e-repurchase - Endang Tjahjaningsih; Dian Suprapti; Euis Soliha; Tristiana Rijanti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Digital technology makes hotel bookings through online travel agents more attractive and more and more people want to make online travel booking agents create more attractive features for hotel bookings. The purpose of this study was to examine the effect of E-WoM on E-repurchase, especially in hotel bookings through Online Travel Booking Agent.com in Semarang City. The method used is an experimental research method using 56 participants using a different test-One Way Annova. The results of the study show that there are differences in the effect of E-WoM on e-repurchase in the form of positive and negative customer reviews from Online Travel Booking Agent XYZ customers. So with these positive reviews, consumers will make repeat purchases at the same e-commerce company. If the previous transaction was unsatisfactory, the customer who will make a repurchase will become less trusting, thereby reducing the intention to repurchase from the e-commerce company.